Eating behavior of adult women during the pandemics - Araújo, Nathália Cavalcanti de Morais; Paixão, Júlia Acioli; Melo, Nathalia Caroline de Oliveira; Silva, Laura Alexia Ramos da; Cabral, Poliana Coelho; Santana, Raquel Araújo de; Ambrose, Carmen Lygia Burgos; Silva, Silvia Alves da; Nascimento, Elizabeth do (Seven Editora, 2023)
The pandemic caused by the spread of the SARS-CoV-2 virus has caused several behavioral changes in the population, including eating behavior. This study aimed to evaluate the eating behavior of adult women in the Metropolitan Region of Recife during the lockdown period due to SARS-CoV-2 pandemic. Data collection was carried out through an electronic form with 431 women. The questionnaire contained questions about anthropometric data, social distance following, and the TFEQ-R21 questionnaire covering eating behavior and emotional feeding. The results obtained were that 80.5% of women were socially distant. About 37% of women were overweight, and 90.3% reported perceiving weight variation during the confinement period. An estimate of the risk of gaining or losing weight as a function of body condition was not found before and during social confinement. As for the TFEQ-R21 questionnaire, the domains addressed showed a positive correlation with weight variations in some of its items. It was concluded that an adverse emotional situation arising from a pandemic situation favors emotional eating. It is suggested that individualized nutritional care is necessary for the creation of efficient methods that aim to improve the relationship with food and to prevent the emergence of future eating disorders. DOI:https://doi.org/10.56238/emerrelcovid19-040